Emergence of a Clinical Escherichia coli Sequence Type 131 Strain Carrying a Chromosomal blaKPC–2 Gene - Wang, Dairong; Mu, Xinli; Chen, Ying; Zhao, Dongdong; Fu, Ying; Jiang, Yan; Zhu, Yiwei; Quan, Jingjing; Hua, Xiaoting; Mao, Guofeng; Li, Xi; Yu, Yunsong (Frontiers in Microbiology, 2020)
Objectives: Bacteria carrying the Klebsiella pneumoniae carbapenemase genes have rapidly spread worldwide and have become a great threat to public health. The blaKPC–2 gene has been primarily located on plasmids cocirculating in various strains. However, chromosomal integration of the blaKPC–2 gene in Escherichia coli has not been reported. In the present study, we report the detection of the first clinical strain of E. coli ST131 with a blaKPC–2 gene, which integrated in the chromosome. E. coli strain EC3385 was identified and subjected to susceptibility testing and genotyping. The complete genome sequences of this strain and four Proteus mirabilis strains were obtained. Chromosomal integration of the blaKPC–2 gene was confirmed using a combination of short- and long-read sequencing. Comparative genetic analyses were performed and the origin of the chromosomal location of the blaKPC–2 gene was further analyzed. Whole-genome sequencing revealed that strain EC3385 belonged to the ST131 type and possessed various resistance and virulence genes. Sequence analysis showed that the blaKPC–2 gene was carried in a 24-kb insertion sequence on the chromosome. This insertion sequence possessed high sequence similarity to previously reported blaKPC–2-habouring plasmids of P. mirabilis in China. To the best of our knowledge, this is the first report of a clinical ST131 E. coli strain carrying blaKPC–2 on the chromosome. The blaKPC–2 gene was probably horizontally transferred from the P. mirabilis plasmid to the E. coli chromosome by the IS26 element, indicating that P. mirabilis might be an important reservoir of blaKPC–2 gene for E. coli. Furthermore, the E. coli ST131 strain carrying the chromosomal blaKPC–2 gene could be further spread due to its carbapenem resistance and high virulence. It is imperative to perform active surveillance to prevent further dissemination of KPC-2 type carbapenemase-producing isolates.